Morals and Personality of Botchan in Natsume Soseki's Botchan - Wido Retno (Lakon : Jurnal Kajian Sastra dan Budaya, 2022)
This study aims to determine the moral values and personality of a character named Botchan in the novel Botchan by Natsume Soseki. This research utilizes a qualitative method by collecting written data in the form of quotations from the novel and analyzing them based on a literary-psychological approach. This study focuses on the main object of research, namely the moral and personality values of the Botchan character. The data were collected using the documentation method and sourced from the text from Novel Botchan by Natsume Soseki. Analysis of the moral values and personality of Botchan as a character encompasses two main layers, namely; 1) human relations with conscience, consisting of attitudes that are not greedy, responsible, sticking to principles, being patient, honest, persistent, and brave, and 2) relationships between human beings, consisting of concern for the suffering and sadness of professional friends and other people who have high honesty like Kiyo. The personality obtained from the Botchan character consists of three aspects, namely 1) the Id (the primitive part of the subconscious that becomes the repertoire of uncontrolled desire), 2) the Ego (balancing the subconscious to reality), and 3) Superego (according to the norms prevailing in society). The result of the research shows that Botchan's character has complex moral values ​​and personality, where Botchan's humanist morality contradicts the individualism which is quite significant.